BEHAVIORAL CRITERIA USED BY THE TECHNICAL EVALUATION OF PERFORMANCE SPORT OF SOCCER (Fiep Bulletin - online, 2011)
The selection processes ("peneirões") developed by technical observers (scouts) are summarized in the observation of the sports performance of a large group of players in a period of several minutes given to each player. And if they are identified promising players in this squad, they are referred to the club for a new observation, which will be conducted by the official category in question. However, the absence of common criteria and performance indicators between these professionals can hinder the evaluation of players as well as be a costly activity for the club. This study proposes to identify and characterize the criteria used by staff of the academy of Andhra Pradesh to assess the sporting performance of young players, in order to compare the criteria for assessing the performance of sports players, used by technicians with different times experience. The study contained 46 categories of technical base of the RN. And the results show that the most important feature, according to those interviewed was the behavior, the 2nd most important characteristic considered was the motivation, the 3rd was the ability, the 4th was the physical condition and was last affiliation.
Keywords: Football; Evaluation; Performance Sports